Perencanaan dan Implementasi Sistem Pembangkit Listrik Tenaga Surya pada Instalasi Pengolahan Air - Tomi Haria Putra; Yani Ridal; Rosnita Rauf (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2026)
This study aims to design and evaluate an on-grid Solar Power Generation System (PLTS) for the Water Treatment Plant (IPA) Taban III in Lubuk Minturun, Padang, addressing the lack of research on on-grid PLTS in government-operated water treatment facilities. Using an engineering design approach, the study covers energy load analysis, Helioscope simulation, and economic feasibility assessment. The site has an average daily solar irradiance of 4.91 kWh/m²/day. The total facility load is 34.32 kW (40,376.47 VA). The PLTS is designed to supply 20% of this, prioritizing a 2.3 kW active load with daily energy demand of 13.8 kWh. The proposed system consists of 27 monocrystalline solar panels (550 Wp) and a 20 kW three-phase grid-tied inverter. Simulation results show an annual energy output of 19,287.9 kWh and a Performance Ratio of 78.06%. The PLTS supplies approximately 59% of daily load demand, with the remaining 41% from the PLN grid via net metering. Deviation between manual calculations and simulation is below 0.5%. Total investment is IDR 239,250,476 with annual savings of IDR 23,419,400, yielding a payback period of approximately 10 years and 3 months. The system is feasible and supports national renewable energy targets, and is recommended for similar public utility facilities.